Accurate molecular weight determination of small molecules via DOSY-NMR by using external calibration curves with normalized diffusion coefficients12. Issue 6 (18th June 2015) - Neufeld, Roman; Stalke, Dietmar
<x xml:space="preserve">Abstract</x> We describe a novel development of MW-determination by using an external calibration curve approach with normalized diffusion coefficients.